An Examination of External Influences and Internal Issues Challenging Teacher Education Today - Jill Gonzalez-Bravo; Donna Augustine-Shaw (The Advocate, 2016)
Today’s educators are not solely content experts, but reflective practitioners competent in theory and complex learning processes. They are obligated to construct classrooms to meet the diverse needs of each child within a culture of global competition and increased levels of accountability. Prior studies amplify a necessary focus on preparing teachers capable of meeting the needs of each student from day one on the job. However, a myriad of obstacles facing teacher preparation identified throughout research provide clear direction for additional attention. The following is an investigation of external influences and internal issues that challenged the current model of teacher preparation programs. Insights may serve to inform teacher educator research and support programs in the professional development of future teachers. Historically teacher education programs have undergone sharp criticisms in regards to their influence on teacher effectiveness (Book & Freeman, 1986; Cochran-Smith & Zeichner, 2005; Cole & Knowles, 1993; Hollingsworth, 1989; Holt-Reynolds, 1992; Reynolds, Ross, & Rakow, 2002; Weinstein, 1990; Zeichner & Tabachnick, 1981). However, many researchers recognized the central role preparation programs played in equipping effective educators with important entry-level knowledge and skills (Boyd, Grossman, Loyd, & Wyckoff, 2009; Darling-Hammond & Bransford, 2005, Fullan & Stiegelbauer, 2007; Hamilton & Pinnegar, 2001; Korthagen, 2004; RESPECT, 2012; Sprinthall, Reiman, & TheisSprinthall, 1996; Wilson, 2009). Interestingly, Cochran-Smith (2003) recognized that “teacher educators - those who teach the teachers - are now the linchpins in educational reforms of all kinds” (p. 5). Despite these noted accolades, the myriad of identified obstacles noted throughout research on the effectiveness of preparation programs warrants investigation. The following article highlights discussion of the external global and national influences and internal program issues that challenge the practice of teacher educators (TE) and the preparation of teacher candidates (TC).